Positioning Strategis Layanan Data Center Cleaning di Pasar B2B Indonesia: Studi Kasus PT XYZ Indonesia - Farry Ramandha (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the strategic positioning of data center cleaning services implemented by PT XYZ Indonesia in Indonesia's Business-to-Business (B2B) market. The research uses a qualitative descriptive approach with a single case study. Data was collected through semi-structured interviews with company management and corporate clients, as well as document analysis. The findings reveal that PT XYZ Indonesia positions itself as a certified international service provider with differentiation based on technical reliability, global reputation, and long-term partnerships. This strategy strengthens customer trust and perceived value, creating competitive advantages in the B2B market, which is highly sensitive to quality and reputation. The study highlights the importance of value-based positioning in technical service sectors, particularly in the data center industry.